The influencing factors of the participation intention and behavior in organized scientific research of young teachers in modern industrial colleges—based on the theory of planned behavior and normative activation theory - Yuanbao Zhang; Junfeng Li; Jinyu Song (Frontiers in Psychology)
Organized scientific research is vital to implementing organized technological innovation in modern industrial colleges. Young teachers’ deep participation determines success. Based on the theory of planned behavior and normative activation, a survey of 309 young teachers from modern industrial colleges participating in organized scientific research found that personal norms, subjective norms, behavioral attitudes, and perceived behavioral control significantly impact their intention to participate. Awareness of consequence, ascribed responsibility, and subjective norms indirectly positively impact their participation intention, and the participation intention and perceived behavioral control positively affect their participation behavior. Policy support has a positive mediating effect between participation intention and behavior. There are group differences in gender, education level, professional title, and subject type in demographic characteristics in five aspects: subjective norms, personal norms, perceived behavioral control, participation intention, and participation behavior. This article proposes the following measures: improving the internal interest coordination mechanism of scientific research organizations to enhance young teachers’ sense of scientific research achievement; reconstructing the organized scientific research evaluation model to enhance young teachers’ teamwork awareness; improving the support system for organized research policies to stimulate young teachers’ self-efficacy; concerning young teachers’ group differences and creating a research environment that tolerates failure.